A STUDY OF THE INHIBITORY EFFECT OF ASPIRIN ON PLATELET AGGREGATION INDUCED BY ADENOSINE DIPHOSPHATE - Din, Jalal -ud-; Nawaz, Shah; Khan, Hidayat Hussain (Journal of Ayub Medical College Abbottabad, 2000)
Background: Aspirin in low dose is a commonly used drug in the prophylaxis of platelet aggregation. This study was done to observe the inhibitory effect of Aspirin on platelet aggregation induced by adenosine diphosphate. Methods: Platelet rich plasma was prepared from the blood of 36 male and 35 female subjects. Adenosine diphosphate was used as an aggregating agent. Reduction in platelet aggregation by aspirin was observed by the method of Born and Mustard. Results: It was found that there was 5.96% reduction in the platelet aggregation due to aspirin. Conclusion: It is concluded that aspirin has significant inhibitory effect on platelet aggregation induced by adenosine diphosphate.